2020
DOI: 10.1007/s12144-020-01081-9
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, attachment, and relationship satisfaction among heterosexual college student couples: An actor-partner interdependence model analysis

Abstract: Interest in mindfulness and relationship satisfaction is increasingly growing. However, although partners in a relationship have mutually interacted, there are few studies exploring this from a dyadic perspective. Thus, this research aims to investigate this dyadic association and furthermore the mediating role of attachment-related process, attachment avoidance and anxiety via Actor-Partner Interdependence Model. Participants of the study were 196 heterosexual college student couples, 196 males' average age 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Empirical research has consistently found negative links between mindfulness and attachment anxiety and avoidance (Stevenson et al, 2017). For example, Zhou et al (2020) found that greater general mindfulness was associated with lower attachment anxiety and avoidance, which in turn predicted higher relationship satisfaction. However, most empirical evidence in this domain comes from correlational, cross-sectional data attained at one time point (e.g., Caldwell & Shaver, 2013; Pepping et al, 2014).…”
Section: Attachment Theory and Attachment Changementioning
confidence: 99%
“…Empirical research has consistently found negative links between mindfulness and attachment anxiety and avoidance (Stevenson et al, 2017). For example, Zhou et al (2020) found that greater general mindfulness was associated with lower attachment anxiety and avoidance, which in turn predicted higher relationship satisfaction. However, most empirical evidence in this domain comes from correlational, cross-sectional data attained at one time point (e.g., Caldwell & Shaver, 2013; Pepping et al, 2014).…”
Section: Attachment Theory and Attachment Changementioning
confidence: 99%
“…In addition, when suburban high school students demonstrate excellent mindfulness, it can aid them in processing received material and regulating cognitive abilities during learning, thereby influencing academic achievement (Bóo et al, 2020). When students do not demonstrate mindfulness, however, suburban high school students tend to doubt themselves, which increases their anxiety and fear of being ignored by others (Zhou, Lin, Li, Du, & Xu, 2022). Low levels of mindfulness can also make students less adaptable, prone to depression, and apprehensive during the school learning process (Bravo, Boothe, & Pearson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These interventions, indirectly, could therefore promote the development of secure attachment in the couple. However, a recent study shows that a high level of mindfulness in one partner does not necessarily lead relationship satisfaction for both(Zhou, Lin, Li, Du, & Xu, 2022…”
mentioning
confidence: 96%